Modernization of Islamic Education From a Fiqh Perspective - Rini Nopita; Chanifudin, Chanifudin (Sean Institute, 2025)
Modernization of Islamic education is a challenge in facing the changing times. Islamic education needs to continue to develop in order to be relevant to the needs of society without neglecting sharia values. This article discusses how the fiqh perspective can be the foundation in the process of modernizing Islamic education. Modernization of Islamic education is an effort to combine traditional Islamic values with the demands of the times. In the fiqh approach, Islamic education must consider the principles of sharia that emphasize the balance between spiritual, moral, and intellectual aspects. This study uses a qualitative method with a literature study approach, examining the views of contemporary scholars as well as classical fiqh sources. The results show that the modernization of Islamic education can be done in a shari'i manner while maintaining the maqashid of sharia, such as the protection of faith, reason, and morality. This study concludes that Islamic fiqh provides flexibility to respond to the dynamics of the times, as long as educational innovation does not contradict the principles of sharia.